PENGARUH TERAPI BERMAIN PUZZLE TERHADAP KECEMASAN PADA ANAK USIA PRASEKOLAH (3-6 TAHUN) YANG MENJALANI HOSPITALIASI DI RSUD EMBUNG FATIMAH BATAM - Indah Purnamasari; Elvi Murniasih; Virisya Chumaerotusyfa (Journal of Hospital Administration and Management, 2021)
World Health Organization (WHO) in 2017 stated that in the United States, estimated more than 5 million children undergoing hospitalization because surgical procedures and for more than 50% of the total the children experience anxiety and stress. In Embung Fatimah Hospital Batam (2019) the numbers of anxiety in preschool children (3-6 years) is high enough as many as 20 of them on average experienced moderate anxiety level. When chidren hospitalization they try to adapt the new envirmen in the hospital So that these conditions will impact stressors, fears and anxiety in children. If anxiety is not controlled will have an impact on treatment procedures, such as the child is uncooperative toward hospital staff (nurses and doctors). The purpose of this study to determine whether there are the influences of therapeutic play : puzzle on anxiety of hospitalized preschool children (3-6 years) in Embung Fatimah Hospital Batam. The research was quasy Experiment with pretest and posttest research methods Design Without Control, using a total sampling with 20 respondents. Statistical test in this study using the Wilcoxon. By the result observation before therapy puzzles children undergoing hospitalization experience moderate anxiety as many as 14 people (70%) and some of responden experience mild anxiety as many as 6 people (30%). After therapy puzzles, as many as 15 people (75%) of children undergoing hospitalization from 20 respondents did not experience anxiety and 5 people (25%) experienced mild anxiety. The results after therapy puzzles, p-value of 0.000 or> 0.05. So it can be concluded that there is an influence after therapy puzzles on anxiety of Hospitalized Children Preschoolers (3-6 years). At nursing is expected to be applied as a method to provide comfort to children preschoolers (3-6 years) who undergoing hospitalization in order not to feel anxious.